Merkantilista csírák Bethlen tündérkertjében : a fejedelmi hatalom gondolati "externáliái" - Barancsuk, János (Közép-Európai Közlemények, 2014)
The first third of 17th century is a „heroic" but also a hard era, and it brings the encounter of a man growing up for his tasks and the leader who stands an example for next eras in Transylvania. The essay’s aim is to „categorize" Bethlen Gábor’s economic policy. Throughout the essay we try to form an opinion as if the instructions given by the monarch, the power system he worked on were alltogether to serve in mercantilistic way the raison and the common good. Since there is still no „healthy" consense about the basics od mercantilism in the academic knowledge, we believe it is necessary to introduce the subject breafly, connecting it with the cogitation on the economic processes coordinated by the mechanisms’ and absolutism’s relationship. The period of Bethlen, for today’s era is a root of somé kind of „crosstalk": serves as excellent additions to make an assumption in the evergreen „government and/or markét" debate, in the understanding of understanding „historical personalities" roles, moreover it might be a good help when speculating on the highlights of democracy as well.